2017
DOI: 10.3758/s13423-017-1360-2
|View full text |Cite
|
Sign up to set email alerts
|

Bias and ignorance in demographic perception

Abstract: When it comes to knowledge of demographic facts, misinformation appears to be the norm. Americans massively overestimate the proportions of their fellow citizens who are immigrants, Muslim, LGBTQ, and Latino, but underestimate those who are White or Christian. Previous explanations of these estimation errors have invoked topic-specific mechanisms such as xenophobia or media bias. We reconsidered this pattern of errors in the light of more than 30 years of research on the psychological processes involved in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…This interpretation is consistent with a recent study by Kirkegaard and Bjerrekaer [6], who found that Danish people's estimates of welfare use rates for 70 origin country groups correlated at r = 0.70 [0.55, 0.80] with the actual use rates for those groups. Both of the preceding findings are in line with a larger body of research on stereotype accuracy for demographic groups [7][8][9][10]. (Note that both Carl's [5] and Kirkegaard & Bjerrekaer's [6] effect sizes correspond to consensual stereotype accuracy correlations [9].…”
Section: Introductionsupporting
confidence: 78%
“…This interpretation is consistent with a recent study by Kirkegaard and Bjerrekaer [6], who found that Danish people's estimates of welfare use rates for 70 origin country groups correlated at r = 0.70 [0.55, 0.80] with the actual use rates for those groups. Both of the preceding findings are in line with a larger body of research on stereotype accuracy for demographic groups [7][8][9][10]. (Note that both Carl's [5] and Kirkegaard & Bjerrekaer's [6] effect sizes correspond to consensual stereotype accuracy correlations [9].…”
Section: Introductionsupporting
confidence: 78%
“…This interpretation is consistent with a recent study by Kirkegaard & Bjerrekaer (2016), who found that Danish people's estimates of welfare use rates for 70 origin country groups correlated at r = .70 [.55, .80] with the actual use rates for those groups. 4 Both of the preceding findings are in line with a larger body of research on stereotype accuracy for demographic groups (Jussim, 2012;Jussim, Crawford, & Rubinstein, 2015; and see Landy, Guay & Marghetis, 2017).…”
Section: Introductionsupporting
confidence: 72%
“…One major implication of this conclusion is that public beliefs about immigrants are more accurate than is often assumed (e.g., Caplan, 2007;Nardelli & Arnett, 2014;Sohoni & Sohoni, 2016). Indeed, it is frequently asserted that the public beliefs about immigrants are largely erroneous, given that Europeans typically overestimate the immigrant fraction of the population by 10-15 percentage points (Nardelli & Arnett, 2014; but see Landy, Guay & Marghetis, 2017). Yet building on previous research (Carl, 2016;Kirkegaard & Bjerrekaer, 2016;Jussim, 2012;Jussim, Crawford, & Rubinstein, 2015), our study indicates that the Danish public has remarkably accurate beliefs about the relative positions of different origin country groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the availability heuristic, we tend to see our own groups as superior to others (13) and are often prone to myside bias (14). Further, people often overestimate small percentages of events, even when not estimating their own groups' contributions (15,16). Any or all of these factors may be involved in the phenomenon of collective narcissism.…”
mentioning
confidence: 99%